2019
DOI: 10.3390/molecules24203682
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effects of IL-1β Combined with IL-17A Promoted Cartilage Degradation and Suppressed Genes Associated with Cartilage Matrix Synthesis In Vitro

Abstract: Combinations of IL-1β and other proinflammatory cytokines reportedly promote the severity of arthritis. We aimed to investigate the effects of IL-1β combined with IL-17A on cartilage degradation and synthesis in in vitro models. Cartilage explant degradation was determined using sulfated glycosaminoglycans (S-GAGs) levels, matrix metalloproteinase (MMP13) gene expression, uronic acid, and collagen contents. Cell morphology and accumulation of proteoglycans were evaluated using hematoxylin-eosin and safranin O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. Some studies have used a combination of mechanical injury and inflammatory cytokine treatment, typically using IL-1α, IL-1β, TNF-α, IL-17, or the combination of TNF-α/IL-6/sIL-6R [ 143 , 144 , 145 , 146 , 148 , 152 , 154 ] to mirror trauma and the presence of cytokines that are significantly present with the injured knee.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
See 3 more Smart Citations
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. Some studies have used a combination of mechanical injury and inflammatory cytokine treatment, typically using IL-1α, IL-1β, TNF-α, IL-17, or the combination of TNF-α/IL-6/sIL-6R [ 143 , 144 , 145 , 146 , 148 , 152 , 154 ] to mirror trauma and the presence of cytokines that are significantly present with the injured knee.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
“…Articular cartilage explant and in vitro chondrocyte studies, using cells or tissue derived from either OA or healthy sources have shown that IL-1α treatment alone is capable of increasing production of MMP-1, 3, 9 and -13 and ADAMTS-4 and -5, decreasing proteoglycan synthesis and increasing the loss of sGAG [ 144 , 148 , 149 , 155 , 156 , 157 ], while IL-1β alone is capable of enhancing NO production, collagenase activity, IL-6, IL-8, LIF, MMPs (MMP-1, -3, -13, -7, -9, -12), complement components, chemokines as well as aggrecan release; and inhibiting type II collagen, NF-ĸB binding activation and phosphor-Smad2/3 [ 69 , 147 , 152 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. These studies, as well as animal models, showed that IL-1β is involved in inflammation and cartilage degradation.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, Comb48 seemed to enhance the expression of these anabolic genes, which may suggest the benefit of HA when combined with CAR. Nevertheless, we have suggested that chondrocytes be more deeply investigated for further use in 3D culture models, such as those involving pellet or scaffold cultures (Kongdang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%